2005
DOI: 10.1590/s0074-02762005000300008
|View full text |Cite
|
Sign up to set email alerts
|

A follow up study of cytomegalovirus infection in a group of Turkish renal transplant recipients using molecular assays

Abstract: The clinical value of an in-house cytomegalovirus nested polymerase chain reaction (CMV-PCR) and a commercial molecular assay hybrid capture CMV DNA assay (HCA) was evaluated in monitoring a group of renal transplant patients for six months follow up. In this study, the sensitivity, specificity, positive predictive value, and negative predictive value of nested CMV DNA PCR assay and HCA at the beginning of the study were 70, 42.9, 46.7, 66.7, and 60, 78.6, 66.7, and 73.3% respectively. After six months, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…3 After transplant, periods of ischemia and then reperfusion renders the release of various inflammatory mediators, 23,28 which are important in T-cell differentiation and even graft destructive immune cells. 28,29 One study group reported that the factors, which are released by endothelial cells during ischemia-reperfusion injury, can increase production of some cytokines like IL-17 and IFN-γ by CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 After transplant, periods of ischemia and then reperfusion renders the release of various inflammatory mediators, 23,28 which are important in T-cell differentiation and even graft destructive immune cells. 28,29 One study group reported that the factors, which are released by endothelial cells during ischemia-reperfusion injury, can increase production of some cytokines like IL-17 and IFN-γ by CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 In rat acute renal allograft rejection models, elevation of IL-17 proteins in day 2 after transplant has been shown. 22,23 In mouse heart transplant model, using IL-17 inhibitor, reduced production of inflammatory cytokines within the graft and increased graft survival. 24 The role of Th17 and IL-17 in liver transplant is not studied much in humans, but reported a significant increase of IL-17/IL-23 protein level in patients with acute rejection after liver transplant; 25,26 Also, our recent study 4 showed the increase of IL-17 mRNA level in the first week after liver transplant in rejected ones.…”
Section: Introductionmentioning
confidence: 99%